2016
DOI: 10.1161/atvbaha.116.308027
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Versus Monogenic Causes of Hypercholesterolemia Ascertained Clinically

Abstract: F amilial hypercholesterolemia (FH) is a relatively common disorder, previously thought to have a monogenic basis. 1 The paradigmatic heterozygous form of FH (HeFH) is characterized by lifelong elevations in plasma low-density lipoprotein (LDL) cholesterol, typically >5.0 mmol/L (194 mg/dL), sometimes occurring with characteristic physical signs and frequently with a personal or family history of early cardiovascular disease (CVD).1 Recent populationbased surveys, including screening with DNA sequencing, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
148
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 20 publications
8
148
1
6
Order By: Relevance
“…The overall detection rate of pathogenic/likely pathogenic variants was around 60%, a figure which is comparable to that obtained in other studies [12,13]. The assignment of pathogenicity was based on in silico analysis using several algorithms [4] and information available in the published variant databases.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The overall detection rate of pathogenic/likely pathogenic variants was around 60%, a figure which is comparable to that obtained in other studies [12,13]. The assignment of pathogenicity was based on in silico analysis using several algorithms [4] and information available in the published variant databases.…”
Section: Discussionsupporting
confidence: 72%
“…Several reports have shown that a variable percentage (20e40%) of patients with the clinical diagnosis of heterozygous FH do not carry mutations in the candidate genes mentioned above [12]. Some of these patients were found to carry a burden of LDL-cholesterol (LDL-C) increasing gene variants which cumulatively raise LDL-C levels into the heterozygous FH range [12,13]. However, there are patients in whom the polygenic effect does not explain the high LDL-C levels, indicating the possible presence of other genes yet to be identified [13].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale, whole-exome sequencing studies suggest that HeFH has a prevalence of ~1 in 217 (0.46%) northern European individuals 39. At the upper end of the number of patients with HeFH eligible for ALI or EVO, in 313 patients with severe hypercholesterolemia (LDLC >194 mg/dL), Wang et al40 reported that 47.3% had monogenic familial hypercholesterolemia, 53.7% if polygenic scores were present, and 67.1% with extreme polygenic scores.…”
Section: Discussionmentioning
confidence: 99%
“…53 For instance, in 313 patients with FH who were evaluated using a targeted next-generation sequencing panel and an assay to detect large-scale copy-number variation, Wang et al 54 found a genetic basis for extremely elevated LDL-C in ≈67% of patients. Of these individuals, 45% had a monogenic largeeffect variant, 6% had a copy-number variation, and 17% had a strong polygenic component, as defined by accumulation of common GWAS-identified SNPs associated with LDL-C levels.…”
Section: Advances In Genetic Dyslipidemiasmentioning
confidence: 99%
“…Of these individuals, 45% had a monogenic largeeffect variant, 6% had a copy-number variation, and 17% had a strong polygenic component, as defined by accumulation of common GWAS-identified SNPs associated with LDL-C levels. 54 Thus, several types of genetic variants need to be considered when assessing patients with elevated LDL-C, including those contributing to both monogenic and polygenic risk. 55 Furthermore, in clinical assessment of patients with severe hypercholesterolemia, it is critical to rule out the contribution of secondary factors, 56 including drugs such as cyclosporine, which can raise LDL-C through both LDL receptor and nonreceptor mechanisms.…”
Section: Advances In Genetic Dyslipidemiasmentioning
confidence: 99%